HUBUNGAN PAPARAN DEBU KAYU DENGAN KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA PEKERJA MEBEL DI PT. X JEPARA - Ibnu Sri Fuqoha; Ari Suwondo; Siswi Jayanti (Jurnal Kesehatan Masyarakat (Undip), 2017)
Finedust is particle of wood produced from wood processing and handling. Levels of finedust in the work environment can be exposed to workers through breathing and cause respiratory infections. Acute Respiratory Infection (ARI) is an acute infectious disease that is attacking one or more parts of the respiratory tract (upper and lower) to the alveolar included adnexal. Workers characteristics can be a risk factor for ARI are age, sex, nutritional status, exercise habits, PPE usage, tenure, medical history, and smoking habits. The purpose of this study to analyze the correlations of finedust exposure with ARI of furniture workers in PT. X Jepara. The type of research is observational cross-sectional study and quantitative analysis methods. The population are 139 production workers of Putty Sandpaper Department, Natural Sandpaper Department and Sanding Sandpaper Department with a minimum sample of 46 workers. The bivariate analysis using Rank Spearman (α = 0.05) showed the correspondent variables were the levels of finedust (ρ Value 0.007), age (ρ Value 0.036), nutritional status (ρ Value 0.005), tenure (ρ Value 0.029). Meanwhile there is no correlation were history of respiratory illness (ρ Value 0.204) and exercise habits (ρ Value 0.410).